Cathedral at Durham
Norman justice operated at four levels: the Manor Courts for the largely slave-labor peasant; the Shire Courts for sheriff justice in the rural districts; the Baronial Courts for the vassals of great houses; and the Church Courts. Sanctuary for an offense committed against another level could be obtained by entry into the precincts of the church, and holding to this knocker gave that right.